Enhancing group B children's ability to recognize the consonant letters b, d, and p using natural materials as learning media - Maesaroh, Yuni; Cucu Sopiah; Muh. Arif Syarief H (Universitas Islam Negeri Raden Intan Lampung, 2026)
Background: Early childhood children's ability to recognize the consonant letters b, d, and p remains relatively low due to the similarities in the shapes of these letters and the limited use of clear and engaging learning media. Objective: This study aimed to improve children's recognition of the consonant letters b, d, and p by utilizing natural materials as learning media for Group B children at Sejahtera Kindergarten. Methods: This study employed a Classroom Action Research (CAR) design conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The participants were 12 children in Group B. Data were collected through observation, documentation, and field notes and were analyzed using qualitative and quantitative approaches. Results: The findings indicated a gradual improvement in children's ability to recognize the consonant letters b, d, and p, increasing from 30.00% (4 children) before the intervention to 50.00% (6 children) in Cycle I and further to 85.00% (10 children) in Cycle II, representing an overall improvement of 55.00% from the initial condition to the end of the study. Conclusion: The findings demonstrate that the use of natural materials as learning media effectively improved Group B children's ability to recognize the consonant letters b, d, and p, while also promoting more meaningful learning experiences that are appropriate for early childhood characteristics.